2020
DOI: 10.1007/s42978-020-00072-3
|View full text |Cite
|
Sign up to set email alerts
|

Coaches’ Evaluations of Match Performance in Academy Soccer Players in Relation to the Adolescent Growth Spurt

Abstract: Individual differences in biological maturation present challenges for coaches involved with youth soccer players. Youth in the same chronological age group vary in terms of stage of maturity (pre, circum-and post-pubescent) and rate of growth, but how this affects coaches' evaluations of player performance is unknown. The aim of this study was to compare youth soccer coaches' evaluations of players match performances before, during and post growth spurt in a professional English soccer academy across four sea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 37 publications
(73 reference statements)
0
21
0
Order By: Relevance
“…Discrete and controlled tests ("signs"), whether conducted in the laboratory or field, lack ecological validity and transference to actual performance within team sports. Accordingly, a samples-based approach may be more appropriate in TID programmes, where judgements are made based on assessments that more closely mimic the context, environment, and task of team sport performance [23,64,81,83], including the subjective expert opinions of relevant staff [84,86,93].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Discrete and controlled tests ("signs"), whether conducted in the laboratory or field, lack ecological validity and transference to actual performance within team sports. Accordingly, a samples-based approach may be more appropriate in TID programmes, where judgements are made based on assessments that more closely mimic the context, environment, and task of team sport performance [23,64,81,83], including the subjective expert opinions of relevant staff [84,86,93].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Bennett et al [81] showed that higher skilled players (trained within a professional academy) had a significantly greater number of attempted and completed skill involvements in SSGs compared with low-level players (trained within a local academy) (p < 0.01). Further research within American Football demonstrated that samples of previous performance, measured via position specific in-game statistics (e.g., percentage pass completion for a quarterback), across a 1-year period at college level, was a statistically significant predictor (p < 0.05) of subsequent performance in the National Football League (NFL), whereas signs of performance (i.e., physical tests in the NFL Combine) failed to demonstrate predictive power of future NFL performance [83]. Equally, in Australian Football, O'Connor et al [64] demonstrated a significant difference in recent match-play performance (sample) between selected and non-selected athletes into a national programme (p < 0.001).…”
Section: Samplesmentioning
confidence: 99%
“…Research has shown growth-related decrements in functionality and performance can temporarily handicap young athletes. 18,32,46 Consistent with this reasoning, coaches described players in the growth spurt as inconsistent or performing below expectations (See Case Study One: The Roller-coaster).…”
Section: : "Having" Growthmentioning
confidence: 84%
“…To better understand how adolescence influences athlete performance and development, a more explorative approach is required. Objective quantitative studies dominate the current literature 32,37 ; very few qualitative studies have been conducted exploring how changes associated with adolescence impact young athletes and their coaches'. 38 A coach's subjective opinion of players' performances and potential is decisive in whether young players are retained or released.…”
Section: Introductionmentioning
confidence: 99%
“…Notwithstanding the obvious focus directly on the young athletes themselves, it is also important to consider the role and potential influence of significant others to the development process for young athletes. To this extent, Hill et al provide original insights into coaches' evaluations of match performance in academy soccer players before, during and after the adolescent growth spurt [6], while De Ste Croix et al report on the differences in knowledge and understanding, attitude and confidence of coaches to deliver injury prevention training in a sample of three European countries [3].…”
mentioning
confidence: 99%